Techno-economic assessment of waste heat recovery technologies for the food processing industry - Mukherjee, Sanjay; Asthana, Abhishek; Howarth, Martin; Chowdhury, Jahedul Islam (MDPI, 2020)
The food manufacturing sector is one of the most dominant consumers of energy across the globe. Food processing methods such as drying, baking, frying, malting, roasting, etc. rely heavily on the heat released from burning fossil fuels, mainly natural gas or propane. Less than half of this heat contributes to the actual processing of the product and the remaining is released to the surroundings as waste heat, primarily through exhaust gases at 150 to 250 °C. Recovering this waste heat can deliver significant fuel, cost and CO2 savings. However, selecting an appropriate sink for this waste heat is challenging due to the relatively low source temperature. This study investigates a novel application of gas-to-air low temperature waste heat recovery technology for a confectionary manufacturing process, through a range of experiments. The recovered heat is used to preheat a baking oven’s combustion air at inlet before it enters the fuel-air mixture. The investigated technology is compared with other waste heat recovery schemes involving Regenerative Organic Rankine Cycles (RORC), Vapour Absorption Refrigeration (VAR) and hot water production. The findings indicate that utilising an oven’s exhaust gases to preheat combustion air can deliver up to 33% fuel savings, provided a sufficiently large heat sink in the form of oven combustion air is available. Due to a lower investment cost, the technology also offers a payback period of only 1.57 years, which makes it financially attractive when compared to others. The studied waste heat recovery technologies can deliver a CO2 savings of 28–356 tonnes per year from a single manufacturing site. The modelling and comparison methodology, observations and outcomes of this study can be extended to a variety of low temperature food manufacturing processes.
Keywords: waste heat recovery; baking; energy efficiency; food manufacturing; organic rankine cycle; vapour absorption cooling